2018
DOI: 10.1161/circinterventions.117.005985
|View full text |Cite
|
Sign up to set email alerts
|

Survival After MitraClip Treatment Compared to Surgical and Conservative Treatment for High-Surgical-Risk Patients With Mitral Regurgitation

Abstract: This matched analysis suggests a lower mortality hazard for MitraClip intervention in a high-risk population with symptomatic mitral regurgitation when compared with conservative management alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 24 publications
0
12
1
Order By: Relevance
“…Recently, the German TRAMI Registry reported an overall 4‐year observed survival after MitraClip of 46.9%, not significantly different between FMR and DMR ( P = 0.45) . Another large multicenter retrospective study showed a 5‐year survival after MitraClip for mixed MR mechanisms of 40% . Both were slightly lower than ours, likely explainable by their higher risk profile (respectively mean STS‐PROM 8.5% and 7.8%).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Recently, the German TRAMI Registry reported an overall 4‐year observed survival after MitraClip of 46.9%, not significantly different between FMR and DMR ( P = 0.45) . Another large multicenter retrospective study showed a 5‐year survival after MitraClip for mixed MR mechanisms of 40% . Both were slightly lower than ours, likely explainable by their higher risk profile (respectively mean STS‐PROM 8.5% and 7.8%).…”
Section: Discussionmentioning
confidence: 80%
“…On the other hand, several large real‐world registries have reported promising early outcomes in patients at increased surgical risk who presented with mitral anatomies both within and outside the conventional EVEREST criteria, and as a matter of fact, the ability of EVEREST criteria to predict the long‐term results after the intervention is currently debated in the literature . Unfortunately, long‐term data from such wide cohorts are still scarce, especially when assessing FMR and DMR separately.…”
Section: Introductionmentioning
confidence: 99%
“…324 Due to their high surgical risk, such patients are now considered candidates for percutaneous repair or replacement of the aortic 325 and mitral valves. 326 In this scenario, CVR can be considered before the intervention, with the aim of decreasing complication rates, length of hospital stay, and mortality and morbidity associated with the frailty syndrome. 327 After the intervention, CVR then provides an opportunity for monitoring and optimization of the outcomes of the procedure in all its aspects.…”
Section: Pre-exercise Evaluationmentioning
confidence: 99%
“…After an initial screening, 14 reports [Niikura 2020;Alozie 2017;Kortlandt 2018;Feldman 2015;Paranskaya 2013;Anwer 2019;Swaans 2014;Taramasso 2012;De Bonis 2015;Buzzatti 2015;Gyoten 2020;Ondrus 2016;Buzzatti 2019;Ostovar 2018] comparing MitraClip with surgical MV repair, enrolling a total of 3355 patients with severe MR, were identified and included in qualitative and quantitative analyses. Only 1 study, the Endovascular Valve Edge-to-Edge Repair Study (EVEREST) II10, was a randomized controlled trial, whereas the others were observational comparative studies (Table 1) [Niikura 2020;Alozie 2017;Kortlandt 2018;Paranskaya 2013;Anwer 2019;Swaans 2014;Taramasso 2012;De Bonis 2015;Buzzatti 2015;Gyoten 2020;Ondrus 2016;Buzzatti 2019;Ostovar 2018]. The late follow-up duration was from 180 days [Ostovar 2018] to 5 years [Feldman 2015] (Tables 1 and 2).…”
Section: Search Resultsmentioning
confidence: 99%